The radio structure of the narrow-line Seyfert 1 Mrk 783 with VLBA and e-MERLIN - Congiu E; Kharb P; Tarchi A; Berton M; Caccianiga A; Chen S; Crepaldi L; Di Mille F; Järvelä E; Jarvis M E; La Mura G; Vietri A (United Kingdom, 2022)
In this paper, we present the analysis of new radio and optical observations of the narrow-line Seyfert 1 galaxy Mrk 783. $1.6\, \mathrm{GHz}$ observations performed with the e-MERLIN interferometer confirm the presence of the diffuse emission previously observed. The Very Long Baseline Array (VLBA) also detects the nuclear source both at $1.6\, \mathrm{GHz}$ (L band) and $5\, \mathrm{GHz}$ (C band). While the L-band image shows only an unresolved core, the C-band image shows the presence of a partially resolved structure at a position angle of 60○. The brightness temperature of the emission in both bands ( ${\gt}10^6\, \mathrm{K}$ ) suggests that it is a pc-scale jet produced by the active galactic nucleus. The relatively steep VLBA spectral index (αVLBA = 0.63 ± 0.03) is consistent with the presence of optically thin emission on milliarcsecond scales. Finally, we investigated two possible scenarios that can result in the misalignment between the kpc and pc-scale radio structure detected in the galaxy. We also analysed the optical morphology of the galaxy, which suggests that Mrk 783 underwent a merging in relatively recent times....